A kitchen‐based intervention to improve nutritional intake from school lunches in children aged 12–16 years. Issue 3 (10th April 2013) - Madden, A. M.; Harrex, R.; Radalowicz, J.; Boaden, D. C.; Lim, J.; Ash, R.
Abstract Background School lunches potentially provide an important source of nutrients for children, although studies have shown that their food choices are not always associated with health benefits. The present study aimed to evaluate the effects of a kitchen‐based intervention on intake from school lunches undertaken in 2005. Methods The three‐phase study comprised a pre‐intervention observation, the intervention itself and a post‐intervention observation. Children aged 12–16 years attending a large, inner‐city, secondary school in London were invited to participate. The intervention consisted of small, practical changes to the school menu with the purpose of reducing total and saturated fat and increasing fruit and vegetable consumption. Intake was evaluated using a weighed technique. Results One hundred and eighty and 198 children participated in the pre‐ and post‐intervention phases, respectively. After the intervention, a significant reduction was observed in mean (SD) intake of total fat [44% (8%) versus 40% (9%) total energy, P < 0.01] and of saturated fat [13% (6%) versus 10% (6%), P < 0.01]. The children also ate significantly more fruit and vegetables [12.0 (10.4) g versus 30.0 (30.5) g total weight, P < 0.001]. However, after the intervention, the mean intakes of total and saturated fat, fruit and vegetables were still significantly below the Caroline Walker Trust guidelines for school lunches. Conclusions The present study shows that total and saturated fat and fruit and vegetable intake from school lunches can be significantly improved by a short, kitchen‐based intervention. Although the benefits were limited, the results support further work in this area.